GUIDELINES ON THE MANAGEMENT OF STABLE ANGINA PECTORIS (ENDING) - K. Fox; M. A. A. Garcia; D. Ardissimo; P. Buszman; P. G. Camici; F. Crea; C. Daly; G. de Backer; P. Hjenmdahl; J. Lopez-Sendon; J. Marco; J. Morais; et al. (Столичная издательская компания, 2015)
The Task Force on the Management of Stable Angina Pectoris of the European Society of Cardiology